Ordinary courage the Revolutionary War adventures of Joseph Plumb Martin - Martin, Joseph Plumb (Wiley-Blackwell, 2013)
This remarkable memoir is one of the most celebrated documents to emerge from the tumult of America's Revolutionary War. The ordinary and yet exceptional experiences of a young soldier in Washington's army are given a new life in this fourth edition, sensitively edited for a modern readership.